Pengaruh Media Pembelajaran PowerPoint Interaktif terhadap Hasil Belajar Pendidikan Pancasila Siswa Kelas IV Sekolah Dasar - Naning Dwi Fitri Dianti; Uci Ulfa Nur’afifah; Miratu Chaeroh (JURNAL ILMU PENDIDIKAN, 2026)
This study aims to analyze the effect of interactive PowerPoint learning media on Pancasila education learning outcomes among elementary school students. The research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The sample consisted of 44 fourth-grade students divided into experimental and control groups. The research instrument was a multiple-choice test that had been validated and tested for reliability. Data were analyzed using paired sample t-test, independent sample t-test, and effect size calculation (Cohen’s d). The results indicated a significant improvement in students’ learning outcomes in the experimental group (p < 0.05). The effect size value of 0.95 suggests a strong practical impact of the intervention. These findings demonstrate that interactive learning media enhance conceptual understanding, student engagement, and learning motivation. Theoretically, this study supports the Cognitive Theory of Multimedia Learning and constructivist approaches in technology-based instruction. The findings highlight the importance of integrating interactive media to improve the quality of Pancasila education in primary schools.